2007
DOI: 10.1007/s10802-007-9115-6
|View full text |Cite
|
Sign up to set email alerts
|

The Attribution of Hostile Intent in Mothers, Fathers and Their Children

Abstract: Child externalising symptoms are associated with a bias towards attributing hostile intent to others. We examined the role of parental attributions in the development of this hostile attribution bias in children. The parents of 134 children aged 5-7 years responded to hypothetical social scenarios examining a) their general tendency to attribute hostile intent to the ambiguous behaviour of others, and b) hostile attributions made specifically to their child. Children's own attributions of hostile intent and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 39 publications
3
38
0
3
Order By: Relevance
“…Although this null finding must be interpreted cautiously in the light of the sample size, our observations echo similarly mixed results across previous studies, in which direct parent-child correlations in hostile attributions have proved difficult to establish. Thus, in addition to numerous null findings (Halligan et al, 2007;Bickett et al, 1996;MacKinnon-Lewis et al, 1999), where positive associations have been identified they have typically been limited to a subset of the sample studied and of the indices of hostile attributions obtained (MacBrayer et al, 2003;Nelson et al, 2008). Variations in the approach taken to the measurement of parental attributions may have contributed to mixed findings, including in the current study.…”
Section: Direct Associations Between Maternal and Child Hostile Attrimentioning
confidence: 89%
See 2 more Smart Citations
“…Although this null finding must be interpreted cautiously in the light of the sample size, our observations echo similarly mixed results across previous studies, in which direct parent-child correlations in hostile attributions have proved difficult to establish. Thus, in addition to numerous null findings (Halligan et al, 2007;Bickett et al, 1996;MacKinnon-Lewis et al, 1999), where positive associations have been identified they have typically been limited to a subset of the sample studied and of the indices of hostile attributions obtained (MacBrayer et al, 2003;Nelson et al, 2008). Variations in the approach taken to the measurement of parental attributions may have contributed to mixed findings, including in the current study.…”
Section: Direct Associations Between Maternal and Child Hostile Attrimentioning
confidence: 89%
“…This effect was not found for mothers and sons, suggesting that attributional style could be transmitted along gender lines (MacBrayer, Milich, & Hundley, 2003). However, Halligan and colleagues (Halligan, Cooper, Healy, & Murray, 2007) found no direct association between parental and child attributions, even when mother-daughter and father-son associations were considered separately. Conversely, Nelson and colleagues (Nelson, Mitchell, & Yang, 2008), found that maternal, but not paternal, hostile attributions were related to child hostile attributions, regardless of child gender.…”
Section: Parental Attribution Biasesmentioning
confidence: 92%
See 1 more Smart Citation
“…Исследования прошлых лет, касающиеся вопро-сов интерпретации намерений, показали, что в не-однозначных ситуациях агрессивные молодые люди наиболее склонны приписывать другим враждебные намерения [21][22][23]. Это свойство получило название «предубежденность о враждебности другого» [24].…”
Section: теория обработки социальной информацииunclassified
“…Furthermore, aggressive children are more likely to attribute hostile and mean-spirited content to social cues that are ambiguous with respect to their underlying intentions (e.g., Dodge 1980;Trachtenberg and Viken 1994). That is, in situations in which it is unclear as to the intent of the stimulus actor and the meaning of the cue, aggressive youths are inclined to interpret them as provocative (e.g., Crick 1995;Halligan et al 2007). This finding has been replicated across varied populations, contexts, and developmental periods (Orobio de Castro et al 2002).…”
mentioning
confidence: 99%